Pemetaan penelitian rasio total asset turnover (TATO) pada perbankan syariah dan konvensional: Studi bibliometrik vosviewer dan literature review - Budianto, Eka Wahyu Hestya; Dewi, Nindi Dwi Tetria (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2023)
This study aims to determine the research mapping regarding the Total Asset Turnover (TATO) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the TATO ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the TATO ratio based on the number of clusters and their items; and (3) mapping research topics around the TATO ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 339 journal publications regarding the TATO ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the TATO ratio are divided into 5 clusters and 104 topic items; (3) based on the mapping of literature review studies, there are 26 topics around the influence of the TATO ratio. The implications and contributions of this research are to map research topics around TATO ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.